2018
DOI: 10.1007/s00221-018-5393-1
|View full text |Cite
|
Sign up to set email alerts
|

Individual preferences in motor coordination seen across the two hands: relations to movement stability and optimality

Abstract: The framework of the uncontrolled manifold (UCM) hypothesis was used to explore variables related to stability of task performance in the two hands of young healthy individuals. Fourteen young adults performed four-finger accurate constant force production tasks interrupted by a voluntary quick force pulse production and by an externally imposed displacement of all fingers. Three groups of variables were used to quantify stability of steady force production: (1) indices of the inter-trial variance were compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…Accordingly, the current findings confirmed the potential relation between bilateral synergetic coordination strategies at the planning level (i.e., between multiple trials) and traditional and temporal structural of motor variability of DOFs produced by two hands at the execution level (i.e., within a single trial). Moreover, our correlation findings supported a proposition that the motor system may prefer the stability strategy from no-vision to vision conditions because we observed greater bilateral motor synergies with reduced bad variability related to advanced task stabilization patterns such as less variable and regular bimanual force outputs 37 . As revealed in a neuroimaging study, force control improvements in the vision condition were significantly related to visuomotor processing with greater parietal cortical activations 44 .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Accordingly, the current findings confirmed the potential relation between bilateral synergetic coordination strategies at the planning level (i.e., between multiple trials) and traditional and temporal structural of motor variability of DOFs produced by two hands at the execution level (i.e., within a single trial). Moreover, our correlation findings supported a proposition that the motor system may prefer the stability strategy from no-vision to vision conditions because we observed greater bilateral motor synergies with reduced bad variability related to advanced task stabilization patterns such as less variable and regular bimanual force outputs 37 . As revealed in a neuroimaging study, force control improvements in the vision condition were significantly related to visuomotor processing with greater parietal cortical activations 44 .…”
Section: Discussionsupporting
confidence: 87%
“…The presence of online visual feedback increased bilateral motor synergies implicating more cooperative motor actions between two hands with the reduction of bad variability components across multiple trials. Freitas and colleagues proposed the stabilityoptimality trade-off phenomenon in human behaviors 37 . Specifically, an optimality strategy represents that the central nervous system selects an optimal motor solution from numerous motor elements (i.e., motor redundancy) by minimizing the variance of force elements produced by two limbs along the UCM line.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of online visual feedback increased bilateral motor synergies implicating more cooperative motor actions between two hands with the reduction of bad variability components across multiple trials. Freitas et al proposed the stability-optimality trade-off phenomenon in human behaviors 27 . Specifically, an optimality strategy postulates that the central nervous system selects an optimal motor solution from numerous motor elements by minimizing the variance of force elements produced by two limbs along the UCM line.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, there is an inherent trade-off between stability and optimality (Park et al, 2010). A recent study has shown that healthy individuals show person-specific signatures when dealing with this trade-off (de Freitas et al, 2019), which may be viewed as personal traits, so far barely explored.…”
Section: The Hot Topicsmentioning
confidence: 99%